2023
DOI: 10.5435/jaaos-d-23-00040
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Patient-Reported Outcome Measures in Clinical Practice and Clinical Decision Making

Abstract: Patient-reported outcome measures (PROMs) are highly effective measures of quality of care and outcomes that matter to patients regarding their physical, mental, and social health. While PROMs have played a notable role in research and registry reporting, they are also useful as clinical tools. Real-time PROM collection can be integrated into routine clinical care with immediate access to scores within the electronic health record. This can be integral when discussing treatment options and using decision aids.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 36 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Examining the differences between GMFCS levels and FMS ratings for PODCI individual scores allows for health care providers to identify, and potentially intervene, in areas that are of meaning to these patients and their families. Utilizing measures that can quantify this patient and caregiver perspective is necessary for shared decision-making and can guide future clinical research to more meaningful areas 30–32 …”
Section: Discussionmentioning
confidence: 99%
“…Examining the differences between GMFCS levels and FMS ratings for PODCI individual scores allows for health care providers to identify, and potentially intervene, in areas that are of meaning to these patients and their families. Utilizing measures that can quantify this patient and caregiver perspective is necessary for shared decision-making and can guide future clinical research to more meaningful areas 30–32 …”
Section: Discussionmentioning
confidence: 99%
“…28 With research and health policy placing increasing value on the patient experience, there is a push toward integrating PROMs into routine clinical care. 30 Doing so, however, requires that physicians have a comprehensive understanding of normative values, reference ranges, and predictive thresholds.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the recognition of a key unmet need for HRQoL measures that foster communication between pet caretakers and veterinarians to guide decisions on routine care in clinical practice and monitor pet HRQoL over time is growing [3][4][5][6]. In human medicine, patient reported outcome (PRO) measures, traditionally used in clinical research, are increasingly being incorporated into clinical practice to capture patient experience and guide clinical decision making [7]. Further, a study aimed at determining if the use of a PRO measure as part of routine orthopedic clinical care is associated with improved patient experience showed that, when a PRO measure was included, patients were significantly more likely to feel that the provider had spent enough time with them, to recommend this provider office to another patient and to rate the provider significantly higher on a scale from 0 to 10 [8].…”
Section: Introductionmentioning
confidence: 99%